2016
DOI: 10.1002/ps.4444
|View full text |Cite
|
Sign up to set email alerts
|

A potential insect growth regulator for cockroach control: design, synthesis and bioactivity of N‐terminal‐modified allatostatin analogues

Abstract: The structure-activity relationship studies suggest that different positions of substituents on the benzene ring of the cinnamic acid can lead to different activities. The para-substitution on the benzene ring plays an important role in inhibiting JH biosynthesis in vitro. Moreover, M11 is considered to be a potential IGR for cockroach control. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 26 publications
(57 reference statements)
0
9
0
Order By: Relevance
“…Briefly, Leu-Rink amide-AM was prepared from Rink Amide-AM resin using the standard Fmoc/tBu chemistry and HBTU/HOBt protocol. 24 Then, to replace amino acids protected by Fmoc (containing an R group) and (E)-3-(4-nitrophenyl)-acrylic acid in turn, Fmoc-Gly-OH and Fmoc-Phe-OH were activated with HBTU, HOBt, and N,N-diisopropylethylamine (DIEA) in dimethylformamide (DMF) for 5 min. Fmoc-Gly-OH and Fmoc-Phe-OH replacing amino acids protected by Fmoc (containing an R group) and (E)-3-(4-nitrophenyl)-acrylic acid were activated in turn with HBTU, HOBt, and N,N-diisopropylethylamine (DIEA) in dimethylformamide (DMF) for 5 min, and couplings were run for 4 h at room temperature.…”
Section: Structural Analysis Of the Modeled Dippu-astrmentioning
confidence: 99%
See 1 more Smart Citation
“…Briefly, Leu-Rink amide-AM was prepared from Rink Amide-AM resin using the standard Fmoc/tBu chemistry and HBTU/HOBt protocol. 24 Then, to replace amino acids protected by Fmoc (containing an R group) and (E)-3-(4-nitrophenyl)-acrylic acid in turn, Fmoc-Gly-OH and Fmoc-Phe-OH were activated with HBTU, HOBt, and N,N-diisopropylethylamine (DIEA) in dimethylformamide (DMF) for 5 min. Fmoc-Gly-OH and Fmoc-Phe-OH replacing amino acids protected by Fmoc (containing an R group) and (E)-3-(4-nitrophenyl)-acrylic acid were activated in turn with HBTU, HOBt, and N,N-diisopropylethylamine (DIEA) in dimethylformamide (DMF) for 5 min, and couplings were run for 4 h at room temperature.…”
Section: Structural Analysis Of the Modeled Dippu-astrmentioning
confidence: 99%
“…5 H17 was therefore considered a lead compound for further exploration of IGRs, and several H17 analogs were found to have good JHinhibiting activity as well as Dippu-AstR binding activity. 19,24 In this study, to find highly active IGRs that disturb JH biosynthesis, the 3D structure of Dippu-AstR was first modeled and qualified using RoseTTAFold (http://robetta.bakerlab. org/) and Structure Analysis and Verification Server (SAVES) (http://services.mbi.ucla.edu/SAVES/).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Using the H17, as the lead compound, Xie et al (2016) designed new AST analogues which exhibited strong potency to inhibit JH production by CA of D. punctata. Recently, Wu et al (2017) designed and synthesized 30 analogues, modified with various substituents on the benzene ring at the N-terminus of the lead compound H17. Depending on their results, all analogues exhibited various effects on JH biosynthesis by CA of D. punctata.…”
Section: Fgl-amide Allatostatinsmentioning
confidence: 99%
“…Although the discovery of the first AST almost forty years ago, the exact mode(s) of action is still unknown or remains poorly understood (Weaver and Audsley, 2009;Stay and Tobe, 2007;Chowański et al, 2016). However, the AST compound H17, as well as Ketomethylene, methyleneamino and Dippu-AST (pseudopeptide analogues of ASTs) had been reported as potent inhibitors of JH biosynthesis in some insects (Nachman et al, 1999;Garside et al, 2000;Bendena and Tobe, 2012;Wu et al, 2017). According to the current literature, Nouzova et al (2015) carried out a study aiming to understand the mode of AST compounds in Aedes aegypti.…”
Section: Mode Of Action Of Fgl-amide Allatostatinsmentioning
confidence: 99%
“…In previous studies, approximately 200 FGLamide AST analogues were synthesized by Yang’s group with the C-terminal pentapeptide as the lead compound. Their results suggested that an aromatic group, a linker of an appropriate length, and an FGLa moiety should appear in bioactive AST analogues. The subsequent study showed an alteration of the peptide backbone.…”
Section: Introductionmentioning
confidence: 99%